Marine turtles as bio-indicators of plastic pollution in the eastern Mediterranean - Emily M. Duncan; Hasan Deniz Akbora; Patrizia Baldi; Damla Beton; Annette C. Broderick; Burak Ali Cicek; Charlotte Crowe-Harland; Sophie Davey; Tess DeSerisy; Wayne J. Fuller; Julia C. Haywood; Yu Jou Hsieh; et al. (Marine Pollution Bulletin, 2024)

Flashing NetLights reduce bycatch in small-scale fisheries of the Eastern Mediterranean - Robin T.E. Snape; Damla Beton; Annette C. Broderick; Lucy C.M. Omeyer; Brendan J. Godley (Fisheries Research, 2024)

Behavioural patterns, spatial utilisation and landings composition of a small-scale fishery in the eastern Mediterranean - Josie L. Palmer; Carina Armstrong; Hasan D. Akbora; Damla Beton; Çiğdem Çağlar; Brendan J. Godley; Kristian Metcalfe; Meryem Özkan; Robin T.E. Snape; Annette C. Broderick (Fisheries Research, 2024)

Diversity and distribution of elasmobranchs in the coastal waters of Cyprus: using bycatch data to inform management and conservation - Martha O’Keefe; Elizabeth G. T. Bengil; Josie L. Palmer; Damla Beton; Çiğdem Çağlar; Brendan J. Godley; Meryem Özkan; Robin T. E. Snape; Annette C. Broderick (Frontiers in Marine Science, 2023)
Introduction Loss of biodiversity in marine ecosystems is a globally acknowledged problem. To address this and avoid extinctions, improved conservation is required to protect and restore our oceans. Elasmobranch species are considered the second most threatened vertebrate lineage, with overfishing considered the most important driver of declines. The Mediterranean Sea is a hotspot for elasmobranchs, with the eastern basin considered a data-poor area. Methods This study sought to address that deficiency, using bycatch data to assess the diversity and distribution of elasmobranch species caught as a result of commercial fishing in Northern Cyprus from 2018 to 2022. Results Thirty-six elasmobranch species were recorded, including 24 new records for Northern Cyprus, representing 41% of all species recorded in the Mediterranean. Of these 36 species, 61% are listed on the IUCN Red List as globally threatened (Critically Endangered, Endangered or Vulnerable). Of the species recorded, 71% of sharks (n=17), and 53% of batoids (skates and rays; n=19) are listed as threatened. We present data on the distribution of captures and size classes and infer life stage from these data. Discussion Our study demonstrates the importance of the coastal waters of Cyprus for multiple life stages of a broad range of elasmobranch species. As most elasmobranchs caught are retained for bait, subsistence or trade, our study has highlighted the need to update the regulations for this small-scale fishery, and led to a recent amendment to prohibit trade in all species listed under the Barcelona Convention.

Increased sample size provides novel insights into population structure of Mediterranean loggerhead sea turtles - Arzu Kaska; Gizem Koç; Doğan Sözbilen; Diryaq Salih; Ashraf Glidan; Abd Alati Elsowayeb; Almokhtar Saied; Dimitris Margaritoulis; Panagiota Theodorou; ALan Rees; Robin Snape; Annette Broderick; et al. (Conservation Genetics Resources, 2023)

Metal accumulation in juvenile and sub-adult loggerhead and green turtles in northern Cyprus - Sude Çelik; Damla Beton; Burak Ali Çiçek; Robin T.E. Snape; Eyup Başkale (Environmental Pollution, 2023)

Basin-wide estimates of loggerhead turtle abundance in the Mediterranean Sea derived from line transect surveys - Andrew DiMatteo; Ana Cañadas; Jason Roberts; Laura Sparks; Simone Panigada; Olivier Boisseau; Anna Moscrop; Caterina Maria Fortuna; Giancarlo Lauriano; Draško Holcer; Hélène Peltier; Vincent Ridoux; et al. (Frontiers in Marine Science, 2022)
Loggerhead turtles are a globally vulnerable species of marine turtle. Broad-scale patterns of distribution and abundance can provide regional managers a tool to effectively conserve and manage this species at basin and sub-basin scales. In this study, combined aerial and shipboard line transect survey data collected between 2003 and 2018 were used to estimate distribution and abundance throughout the Mediterranean Sea. Approximately 230,000 linear kilometers of survey effort, from seven different surveying organizations were incorporated into a generalized additive model to relate loggerhead density on survey segments to environmental conditions. Two spatial density models estimating loggerhead density, abundance, and distribution were generated – one a long-term annual average covering 2003-2018 and another covering the summer of 2018, when a basin-wide aerial survey, the Agreement on the Conservation of Cetaceans of the Black Sea, Mediterranean Sea and Contiguous Atlantic Area Survey Initiative, was performed. Both models were adjusted for availability bias using dive data from loggerhead turtles tagged with time depth recorders. Mean abundance for the long-term average model was estimated as 1,201,845 (CV=0.22). The summer 2018 abundance estimate was 789,244 turtles and covered a smaller area than the long-term average. These estimates represent the first basin-wide estimates of abundance for loggerhead turtles in the Mediterranean not based on demographic models. Both models predicted similar distributions, with higher abundance predicted in the northern Adriatic Sea, central Mediterranean basin, Tyrrhenian Sea, and south of the Balearic Islands. Lower densities were predicted in the eastern Mediterranean Sea and the Aegean Sea. The highest density areas generally did not coincide with previously established adult loggerhead turtle foraging areas, which are typically neritic, indicating the models are predominantly predicting oceanic distributions, where most of the survey effort occurred. Juvenile loggerhead turtles are predominantly oceanic and comprise most of the population, but care must be taken when using these models as they may not accurately predict distribution of neritic foraging areas, where subadult and adult loggerheads can often be found. Despite this limitation, these models represent a major step forward for conservation planning and understanding basin-wide distribution and abundance patterns of this species.

Increased knowledge affects public attitude and perception towards elasmobranchs and support for conservation - MARIOS PAPAGEORGIOU; ELIZABETH BENGIL G.T.; ROBIN SNAPE; LOUIS HADJIOANNOU (Mediterranean Marine Science, 2022)
The tendency of world media to villainize of sharks has likely contributed to a disparity in the distribution of research and conservation resources among threatened marine megavertebrates, with elasmobranchs losing out. Increased public knowledge on elasmobranchs can shape public attitude and foster and gain support for elasmobranch conservation. Through an online survey, this study aimed to evaluate the drivers of public knowledge and examine linkages between awareness of elasmobranchs and attitude toward their conservation. To explore the relationships and effects between the different predicting variables and public elasmobranch knowledge and attitude indices, bi- and multi-variate analysis and a partial least squares path model were used. The results indicated that the average public elasmobranch knowledge of the Cypriot population was moderate and the average public attitude towards elasmobranchs was relatively low. Marine-related activities and marine-related education were highly correlated with increased public elasmobranch knowledge and were the strongest predictors of the partial least squares path model which explained a high degree of variation in elasmobranch knowledge. Public elasmobranch knowledge was highly correlated with public attitude towards elasmobranchs. The findings of this study highlighted the importance of ocean literacy and education and provide insights into the mechanisms for developing and designing successful advocacy actions for elasmobranch conservation.

Dietary analysis of two sympatric marine turtle species in the eastern Mediterranean - Josie L. Palmer; Damla Beton; Burak A. Çiçek; Sophie Davey; Emily M. Duncan; Wayne J. Fuller; Brendan J. Godley; Julia C. Haywood; Mehmet F. Hüseyinoğlu; Lucy C. M. Omeyer; M. Jesse Schneider; Robin T. E. Snape; et al. (Marine Biology, 2021)
Dietary studies provide key insights into threats and changes within ecosystems and subsequent impacts on focal species. Diet is particularly challenging to study within marine environments and therefore is often poorly understood. Here, we examined the diet of stranded and bycaught loggerhead ( Caretta caretta ) and green turtles ( Chelonia mydas ) in North Cyprus (35.33° N, 33.47° E) between 2011 and 2019. A total of 129 taxa were recorded in the diet of loggerhead turtles ( n = 45), which were predominantly carnivorous (on average 72.1% of dietary biomass), foraging on a large variety of invertebrates, macroalgae, seagrasses and bony fish in low frequencies. Despite this opportunistic foraging strategy, one species was particularly dominant, the sponge Chondrosia reniformis (21.5%). Consumption of this sponge decreased with increasing turtle size. A greater degree of herbivory was found in green turtles ( n = 40) which predominantly consumed seagrasses and macroalgae (88.8%) with a total of 101 taxa recorded. The most dominant species was a Lessepsian invasive seagrass, Halophila stipulacea (31.1%). This is the highest percentage recorded for this species in green turtle diet in the Mediterranean thus far. With increasing turtle size, the percentage of seagrass consumed increased with a concomitant decrease in macroalgae. Seagrass was consumed year-round. Omnivory occurred in all green turtle size classes but reduced in larger turtles (> 75 cm CCL) suggesting a slow ontogenetic dietary shift. Macroplastic ingestion was more common in green (31.6% of individuals) than loggerhead turtles (5.7%). This study provides the most complete dietary list for marine turtles in the eastern Mediterranean.

Foraging ecology of Mediterranean juvenile loggerhead turtles: insights from C and N stable isotope ratios - Julia C. Haywood; Paolo Casale; Daniela Freggi; Wayne J. Fuller; Brendan J. Godley; Bojan Lazar; Dimitris Margaritoulis; ALan F. Rees; Jamie D. Shutler; Robin T. Snape; Nathalie R. Swain-Diaz; Stephen Widdicombe; et al. (Marine Biology, 2020)
Bycatch is one of the key threats to juvenile marine turtles in the Mediterranean Sea. As fishing methods are regional or habitat specific, the susceptibility of marine turtles may differ according to inter- and intra-population variations in foraging ecology. An understanding of these variations is necessary to assess bycatch susceptibility and to implement region-specific management. To determine if foraging ecology differs with region, sex, and size of juvenile loggerhead turtles ( Caretta caretta ), stable isotope analysis of carbon and nitrogen was performed on 171 juveniles from a range of foraging regions across the central and eastern Mediterranean Sea. Isotope ratios differed with geographical region, likely due to baseline variations in δ 13 C and δ 15 N values. The absence of sex-specific differences suggests that within an area, all comparably sized animals likely exploit similar foraging strategies, and therefore, their susceptibility to fisheries threats will likely be similar. The isotope ratios of juveniles occupying the North East Adriatic and North Levantine basin increased with size, potentially due to increased consumption of more prey items at higher trophic levels from a more neritic source. Isotope ratios of juveniles with access to both neritic and oceanic habitats did not differ with size which is consistent with them consuming prey items from both habitats interchangeably. With foraging habitats exploited differently among size classes in a population, the susceptibility to fisheries interactions will likely differ with size; therefore, region-specific management approaches will be needed.

Assessing climate change associated sea‐level rise impacts on sea turtle nesting beaches using drones, photogrammetry and a novel GPS system - Miguel R. Varela; Ana R. Patrício; Karen Anderson; Annette C. Broderick; Leon DeBell; Lucy A. Hawkes; Dominic Tilley; Robin T. E. Snape; Matthew J. Westoby; Brendan J. Godley (Global Change Biology, 2019)
Climate change associated sea‐level rise (SLR) is expected to have profound impacts on coastal areas, affecting many species, including sea turtles which depend on these habitats for egg incubation. Being able to accurately model beach topography using digital terrain models (DTMs) is therefore crucial to project SLR impacts and develop effective conservation strategies. Traditional survey methods are typically low‐cost with low accuracy or high‐cost with high accuracy. We present a novel combination of drone‐based photogrammetry and a low‐cost and portable real‐time kinematic (RTK) GPS to create DTMs which are highly accurate ( Caretta caretta ) and green turtle ( Chelonia mydas ) at a key rookery in the Mediterranean. We combined the DTM with 5 years of nest survey data describing location and clutch depth, to identify (a) regions with highest nest densities, (b) nest elevation by species and beach, and (c) estimated proportion of nests inundated under each SLR scenario. On average, green turtles nested at higher elevations than loggerheads (1.8 m vs. 1.32 m, respectively). However, because green turtles dig deeper nests than loggerheads (0.76 m vs. 0.50 m, respectively), these were at similar risk of inundation. For a SLR of 1.2 m, we estimated a loss of 67.3% for loggerhead turtle nests and 59.1% for green turtle nests. Existing natural and artificial barriers may affect the ability of these nesting habitats to remain suitable for nesting through beach migration.

Microplastic ingestion ubiquitous in marine turtles - Emily M. Duncan; Annette C. Broderick; Wayne J. Fuller; Tamara S. Galloway; Matthew H. Godfrey; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; Andrew G. Mayes; Lucy C. M. Omeyer; David Santillo; Robin T. E. Snape; et al. (Global Change Biology, 2019)
Despite concerns regarding the environmental impacts of microplastics, knowledge of the incidence and levels of synthetic particles in large marine vertebrates is lacking. Here, we utilize an optimized enzymatic digestion methodology, previously developed for zooplankton, to explore whether synthetic particles could be isolated from marine turtle ingesta. We report the presence of synthetic particles in every turtle subjected to investigation ( n = 102) which included individuals from all seven species of marine turtle, sampled from three ocean basins (Atlantic [ATL]: n = 30, four species; Mediterranean (MED): n = 56, two species; Pacific (PAC): n = 16, five species). Most particles ( n = 811) were fibres (ATL: 77.1% MED: 85.3% PAC: 64.8%) with blue and black being the dominant colours. In lesser quantities were fragments (ATL: 22.9%: MED: 14.7% PAC: 20.2%) and microbeads (4.8%; PAC only; to our knowledge the first isolation of microbeads from marine megavertebrates). Fourier transform infrared spectroscopy (FT‐IR) of a subsample of particles ( n = 169) showed a range of synthetic materials such as elastomers (MED: 61.2%; PAC: 3.4%), thermoplastics (ATL: 36.8%: MED: 20.7% PAC: 27.7%) and synthetic regenerated cellulosic fibres (SRCF; ATL: 63.2%: MED: 5.8% PAC: 68.9%). Synthetic particles being isolated from species occupying different trophic levels suggest the possibility of multiple ingestion pathways. These include exposure from polluted seawater and sediments and/or additional trophic transfer from contaminated prey/forage items. We assess the likelihood that microplastic ingestion presents a significant conservation problem at current levels compared to other anthropogenic threats.